PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH DALAM PELAKSANAAN ANGGARAN PENDAPATAN BELANJA DAERAH KABUPATEN KAUR - Purnawan, Heru (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
This investigation was carried out to clarify the following problems: 1) Analyze the implementation of the DPRD's supervisory function in the Kaur Regency APBD; 2) Analyze what factors influence the DPRD's supervisory function in the Kaur Regency APBD. The type of research used in this research is qualitative research. This research data was taken from primary data and secondary data. The data collection techniques used were observation, interviews and recording. Data analysis techniques use data reduction, data presentation, and inference/validation. The results of this research show: 1). The DPRD's supervisory function in implementing the Kaur Regency APBD is good and responsible, as evidenced by supervision indicators including: 1) setting standards, 2) measuring work, 3) evaluating performance prices. 2). Likewise with the factors that influence the role of the Kaur Regency APBD in the supervision of the DPRD. The factors that determine the DPRD's performance in implementing the Kaur Regency APBD are internal and external factors that contribute or predict the success of the DPRD in implementing the Kaur Regency APBD very effectively and efficiently.